Freeze-drying of pharmaceutical products: Research and development needs - Sadikoglu, H.; Ozdemir, M.; Seker, M. (Taylor & Francis Inc, 2006)
Significance of pharmaceutical formulation (choosing of correct excipients in optimal quantities), effects of glass transition temperature, importance of theoretical modeling of the process, benefits of optimal control, and the advantages of remote monitoring of the process are presented. Experimental and theoretical research and development needs for the freeze-drying of pharmaceutical products are proposed and discussed.
Keywords: excipients; freeze-drying; freezing; optimal control; pressure rise method